The Anticarcinogenic Activity Of Plants Compounds - Sugiyanto .; B. Sudarto; Edy Meiyanto; Agung Endro Nugroho (Indonesian Journal of Pharmacy, 2003)
The study was conducted to observe the effect of extracts of ngokilo (Gynura procumbens), beluntas (Pluchea indica), murbei (Morus alba) dan tapak doro (Vinca alba) leaves. Showed anticarcinogenic activity on lung tumor growth of mice. In the nex step, compounds having anticarcfinogenic effect was isolated and identified, and evaluated on the cultures of meiloma and Vero cells. The results showed that non-polar fraction of ethanol extract of ngokilo leaves did not have anticarcinogenic activity, whereas the polar fraction show anticarcinogenic activity. At least there were three flavonoids (flavon or flavonol groups) in this polar fraction. It was only two of these flovonoids which could inhibit the growth of myeloma and Vero cells.Key words : ngokilo, Gynura procumbens, anticarcinogenic, flavonoid.